High-Directional Sound Propagation Over the Earth’s Surface - Denis Sergeevich RAKOV; Aleksandr S. RAKOV; Yury A. CHURSIN; Vsevolod V. PAVLICHEV; Artyom O. IGUMNOV (Archives of Acoustics)
The article discusses the issues of accounting the direction pattern of parametric antenna array the propagation of sound over the Earth’s surface. As a radiator, a parametric antenna array is used. A description is given of measuring equipment and experimental research methods. The Delaney-Bezley model was used as a model of the Earth’s surface impedance. The research results showed the importance of accounting the direction pattern of parametric antenna array in predicting the sound pressure level of a propagating acoustic signal over the Earth’s surface. On the example of a difference signal with a frequency of 2 kHz, the calculation of the sound pressure level on a 100-meter path with the influence of the Earth’s surface is shown. The results obtained showed a good agreement between the theoretical calculation and experimental data.